An increase in canopy cover leads to masting in Quercus ilex - Camarero, J. Julio; Albuixech, Jorge; López-Lozano, Raúl; Casterad, M. Auxiliadora; Montserrat-Martí, Gabriel (Trees, 2010)
Masting is the intermittent and synchronous production of large crops, but its relation to tree growth remains elusive despite the ecological relevance of mast seeding. The production of huge fruit crops has been linked to the accumulation and consumption of resources as nutrients and carbohydrates, but no conclusive assessment has supported this assumption. To evaluate if masting takes place once trees’ canopies reach maximum foliage, changes in canopy cover were measured in Quercus ilex susbp. ballota stands before and after a masting event using the normalized difference vegetation index (NDVI). The results on the whole underline that masting in Q. ilex occurred once maximum levels of NDVI and canopy cover were reached. After the masting event, NDVI dropped, leaf shedding increased and trees produced shorter shoots, narrower tree rings and fewer acorns than before the masting event. These ﬁndings support our contention that an increase in canopy cover precedes masting.
Keywords: acorn; canopy cover; Mast seeding; quercus ilex subsp. ballota; Remote sensing

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 18643937
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.